„Plan Marshalla” dla Ukrainy (Politeja, 2023)
„MARSHALL PLAN” FOR UKRAINERussia’s horrific aggressive war against Ukraine is causing immense human suffering, destruction of critical infrastructure, and hundreds of billions of dollars in damage. The international community stands by Ukraine and is determined to support its reconstruction and modernisation towards a sustainable, democratic and prosperous future, in line with its European path. The new Marshall Plan will fundamentally transform post-Soviet Ukraine and will allow for a new Ukraine to be built, forever moving away from the outdated technologies inherited from the ‘Soviet’ era.